22-gauge Co-Cr versus stainless-steel Franseen needles for endoscopic ultrasound-guided tissue acquisition in patients with solid pancreatic lesions - Yuki Tanisaka; Masafumi Mizuide; Akashi Fujita; Ryuhei Jinushi; Rie Shiomi; Takahiro Shin; Kei Sugimoto; Tomoaki Tashima; Yumi Mashimo; Shomei Ryozawa (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims Endoscopic ultrasound-guided tissue acquisition (EUS-TA) using Franseen needles is reportedly useful for its high diagnostic yield. This study compared the diagnostic yield and puncturing ability of EUS-TA using 22-gauge cobalt-chromium (CO-Cr) needles with those of stainless-steel Franseen needles in patients with solid pancreatic lesions. Methods Outcomes were compared between the 22-gauge Co-Cr Franseen needle (December 2019 to November 2020; group C) and stainless-steel needle (November 2020 to May 2022; group S). Results A total of 155 patients (group C, 75; group S, 80) were eligible. The diagnostic accuracy was 92.0% in group C and 96.3% in group S with no significant intergroup differences (p=0.32). The rate of change in the operator (from training fellows to experts) was 20.0% (15/75) in group C and 7.5% (6/80) in group S. Stainless-steel Franseen needles showed less inter-operator difference than Co-Cr needles (p=0.03). Conclusions Both Co-Cr and stainless-steel Franseen needles showed high diagnostic ability. Stainless-steel Franseen needles are soft and flexible; therefore, the range of puncture angles can be widely adjusted, making them suitable for training fellows to complete the procedure.